Avaliação do potencial citotóxico, moluscicida e alelopático dos extratos hidroetanólicos das folhas de Stryphnodendron obovatum Benth - Salgado, Patrícia C.; Costa, Mirian Feliciano da; Massocatto, Adriana Muniz; Laverde Júnior, Antonio; Frei, Fernando; Kolb, Rosana Marta [UNESP]; Santos, Catarina dos [UNESP] (My University, 2013)
Stryphnodendron obovatum Benth. known as barbatimão de folha miúda, is a typical tree of the Midwest and Southeast “Cerrado” regions of Brazil. Several secondary metabolites have been identified in its barks, including tannins, described on the literature as allelochemicals. Beholding to identify a possible allelopathic activity in S. obovatum leaves, we tested hydroethanolic EtOH:H2 O (70% and 50% v/v) extracts, in different concentrations, on the initial development of cucumber (Cucumis sativus L.). Among the results, we highlight the effect of the 50% hydroethanolic extract in inhibiting the formation of the main and the secondary roots and the stimulation of the hypocotyl growth in C. sativus by the 70% hydroethanolic extract, both in all concentrations tested. The cytotoxic activity, evaluated by bioassay toxicity on Artemia salina Leach., was negative for the tested extracts (LC50> 1000 mg.mL-1). Concomitantly, the molluscicidal activity, evaluated against snails of Biomphalaria glabrata Say, presented low acute toxicity of solutions of 70% hydroethanolic extract at concentrations of 128.9 mg.mL-1 and 172.8 mg.mL-1 and values above 250 mg.mL-1 to solutions of 50% hydroalcoholic extract, being therefore considered inactive for these. The results suggest the existence of allelochemicals in the extracts tested and they have low toxicity.

Stryphnodendron obovatum Benth., conhecida popularmente como barbatimão de folha miúda, é uma árvore típica do Cerrado das regiões centro-oeste e sudeste do Brasil. Vários metabólitos secundários foram identificados na suas cascas, dentre eles, os taninos, descritos na literatura como alelopáticos. Procurando avaliar uma possível atividade alelopática das folhas de S. obovatum, foram testados seus extratos hidroetanólico EtOH:H2 O (70% e 50% v/v), em diferentes concentrações, sobre o desenvolvimento inicial de Cucumis sativus L. (pepino). Dentre os resultados obtidos, destacam-se o efeito do extrato hidroetanólico 50% na inibição da formação da raiz principal e das raízes secundárias e o estímulo do extrato hidroalcoólico 70% no crescimento do hipocótilo de C. sativus. A atividade citotóxica, avaliada pelo bioensaio de toxicidade sobre náuplios de Artemia salina Leach. foi negativa para os extratos testados (CL50 >1000 mg.mL-1). Concomitantemente, a atividade moluscicida avaliada frente a caramujos da espécie Biomphalaria glabrata Say, mostrou baixa toxicidade aguda para soluções do extrato hidroalcoólico 70% nas concentrações de 128,9 mg.mL-1 e 172,8 mg.mL-1 e valores acima de 250 mg.mL-1 para soluções do extrato hidroalcoólico 50%, sendo portanto, considerados inativos para estes. Os resultados sugerem a existência de compostos aleloquímicos nos extratos testados e que estes possuem baixa toxicidade.
Keywords: Natural herbicide; Initial growth; Toxicity; Stryphnodendron obovatum; Cerrado; Alelopatia|Herbicida natural; Crescimento inicial; Toxicidade